IPTEKS DIGITALIZATION TREASURY PADA KANTOR WILAYAH DIREKTORAT JENDERAL PERBENDAHARAAN PROVINSI SULAWESI UTARA - Uno, Moudy Olyvia; Alexander, Stanly W. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Management of state finances is certainly inseparable from the development of the era. The more advanced technology is, the easier it should be for management of state finances. Therefore, it is necessary to implement a system that has been digitized so the benefits of this rapid technological development can be felt by all parties. This is what underlies changes in the finance ministry of the Republic of Indonesian especially in the Directorate General of Treasury.Â  The state treasury system and state budget (STSSB) and agency-level financial application system (AFAS) that support file input and adjustment processes in the Directorate General of Treasury and work units are part of digitalization that has been carried out at the Director General of Treasury., so that all facilities offered by technology in this era can lead to superior treasury manager at the world level. Development and improvement not only stop at the system, but also on the human resources that run the system. The quality of human resources should be improved.Keywords : Digitalization, Information, Human Resources, AFAS, and STSSB